مقدرة القصب Phragmites communis والحور Populus nigra على مراكمة عنصري الزنك والكادميوم على جانبي نهر الرميلة في جبلة- اللاذقية - كبيبو, عيسى; نيصافي, إبراهيم; بدا, مصطفى (Latakia University Journal -Biological Sciences Series, 2017)
هدف هذا البحث إلى دراسة مقدرة كل من القصب الشائع Phragmites communis و الحور الأسود Populus nigra F.hamoui على مراكمة عنصري الكادميوم Cd والزنك Zn, المنتشرين بشكل طبيعي على جانبي نهر الرميلة في مدينة جبلة. وذلك خلال عامي 2014 – 2015، وذلك في أربع مكررات لكل عينة, تم تقدير تراكيز العناصر الثقيلة المدروسة (Cd,Zn) باستخدام جهاز التحليل الطيفي بالامتصاص الذري. بلغ متوسط كمية الكادميوم في تربة الموقع المدروس (3.081 ppm) من الوزن الجاف متجاوزاً المجال الطبيعي لمحتوى الترب من الكادميوم والذي يتراوح بين (0.06-1.1 ppm)، أظهرت الدراسة زيادة تركيز الكادميوم في أوراق القصب على ساقه (0.031- 0.055ppm) على التوالي، وقد بلغت قيمة معامل التراكم الحيوي (BF=0.014), أيضاً في نبات الحور ازداد تركيز الكادميوم في الأوراق على تركيزه في الأفرع (0.016-0.034ppm) ppm على التتالي، وكانت قيمة معامل التراكم الحيوي.(BF = 0.02)أما فيما يخص عنصر الزنك فقد بلغت متوسط كميته في تربة الموقع المدروس (116.61)ppm من الوزن الجاف, نجد أنه مرتفع لكنه أدنى من الحد الأعلى الطبيعي (150) ppm، وقد بّينت النتائج أن تركيز الزنك في أوراق القصب 9.05)ppm), بينما تركيزه في الساق (8.03)ppm، وبلغت قيمة معامل التراكم الحيوي (BF=0.07)، كما سجلت النتائج أدنى تركيز للزنك في أوراق الحور و بلغ 5.13)ppm), بينما كان في الأفرع (6.07) ppm. وكانت قيمة معامل التراكم الحيوي(BF = 0.05). ونلاحظ من خلال هذه النتائج أن كمية الزنك في أجزاء نبات الحور متقاربة.this research aimed to study the ability of both reeds (Phragmites communis) and poplar trees (Populus nigra) to accumulate Cd and Zn. Where speared naturally prevail on the sides of the Rumaila River in Jableh town (research site), during 2014-2015. Average amount of Cd on studied site was 3.081 ppm dry weight. Compared with the normal range of soil content from Cd (0.06-1.1 ppm), we found that it is three times the normal upper limit, indicating site contamination with Cd. The study showed that the Cd concentration in the reed shoots was 0.031 ppm, while it was up to 0.055 ppm in leaves than that of shoots. The value of bio-accumulation factor (BF) was 0.014. Also for poplar, the study revealed predominance of leaves over bark with Cd concentration of 0.034 ppm versus 0.016 ppm for poplar bark. BF value was 0.02. Regarding average amount of Zn in the soil of studied site was recorded 116.61 ppm of dry weight. Compared with average range of Zn in different types of soil (40-100 ppm), we find that it is slightly higher than the normal upper limit, showing site contamination with Zn. The study stated that the Zn concentration in reed leaves was 9.05 ppm versus 8.03 in the shoots. BF value was 0.07. Zn concentration in poplar leaves was the lowest at 5.13 ppm versus 6.07 ppm for the bark. We notice from these findings that the Zn amount in the parts of poplar plant is approximate. BF value was 0.05. The statistical analysis showed significant superiority of reed to poplar in terms of Cd accumulation, and the same for Zn.